Nano-shaping of chiral photons - Sunaba Yuji; Ide Masaki; Takei Ryo; Sakai Kyosuke; Pin Christophe; Sasaki Keiji (Nanophotonics)
Localized surface plasmon polaritons can confine the optical field to a single-nanometer-scale area, strongly enhancing the interaction between photons and molecules. Theoretically, the ultimate enhancement might be achieved by reducing the “photon size” to the molecular extinction cross-section. In addition, desired control of electronic transitions in molecules can be realized if the “photon shape” can be manipulated on a single-nanometer scale. By matching the photon shape with that of the molecular electron wavefunction, optically forbidden transitions can be induced efficiently and selectively, enabling various unconventional photoreactions. Here, we demonstrate the possibility of forming single-nanometer-scale, highly intense fields of optical vortices using designed plasmonic nanostructures. The orbital and spin angular momenta provided by a Laguerre–Gaussian beam are selectively transferred to the localized plasmons of a metal multimer structure and then confined into a nanogap. This plasmonic nano-vortex field is expected to fit the molecular electron orbital shape and spin with the corresponding angular momenta.